Fluoride Levels of Human Plasma and Breast Milk - Şener, Yağmur; Tosun, Gül; Kahvecioğlu, Firdevs; Gökalp, Alparslan; Koç, Hasan (European Journal of Dentistry, 2007)
Objectives: The aim of this study was to determine the fluoride levels in breast milk and plasma of lactating mothers who regularly consumed drinking water with low levels of fluoride.Methods: One hundred twenty five healthy mothers aged between 20-30 years old who had given birth within 5-7 days were included in the study. Besides being otherwise healthy, the primary selection criteria stipulated the absence of fluoride supplement consumption one month before delivery. Approximately 5 ml breast milk and 5 ml blood samples were obtained from each participating mother at a hospital setting, where the mothers were scheduled for a regular hospital diet. The blood samples were centrifuged in fluoride-free heparinized polyethylene tubes and stored at -18oC until measurements were made. Breast milk samples were directly refrigerated as with blood samples until measurements. The fluoride concentrations of milk and blood samples were assessed using an ion-selective fluoride electrode combined with an ion analyzer.Results: The fluoride levels of the plasma and breast milk samples were measured as 0.017±0.011 ppm and 0.006±0.002 ppm, respectively. The fluoride concentration of plasma was significantly higher than that of breast milk (P<.01). Correlation analysis revealed a significant relation between the groups (P<.01).Conclusion: A limited level of fluoride transmission from plasma to breast milk was detected. Nevertheless, a significant correlation between the fluoride concentrations of breast milk and plasma was evident. (Eur J Dent 2007;1:21-24)
Keywords: Breast milk; Fluoride; Plasma